Daya Saing Perkebunan dan Kontribusinya terhadap Pertumbuhan Ekonomi Sumatera Utara Masa Covid-19 - SIAHAAN, JELITA (UNIVERSITAS LANCANG KUNING, 2023)
The plantation sub-sector is one of the sub-sectors in agriculture that has the potential to be developed in North Sumatra, namely oil palm, rubber, and cocoa plantations. These commodities have very profitable prospects in the world market. Oil palm, rubber, and cocoa plantation commodities are Indonesia's leading export commodities that have a role in Indonesia's development. This study aims to determine the performance of production, exports in terms of volume and value, and the competitiveness of North Sumatran palm oil, rubber, and cocoa commodities in the last 10 years (2012 – 2021). This study uses secondary data available in print and electronic form provided by statistical data providers in the last 10 years (20012 – 2021). The data used are primary data on the production of oil palm, rubber, and cocoa which are obtained from BPS-North Sumatra every year. Export data is obtained from “North Sumatra Regional Economic Statistics”, which is published by Bank Indonesia North Sumatra Branch every month. Data analysis method is a method used to process research results in order to obtain a conclusion. The method chosen in data analysis must be in accordance with the research pattern and available data variables. The plantation sub-sector is a very consistent sub-sector in terms of production development, exports and competitiveness. In the last 10 years the average production growth of palm oil, rubber, and cocoa has reached 10% per year. One of the superior commodities is oil palm. Based on the results of the study, it can be concluded as follows: Production of North Sumatran palm oil, rubber, and cocoa commodities has fluctuated in the last 10 years. Rubber and cocoa show a downward trend in production, while palm oil shows a positive production trend. In terms of exports, palm oil and cocoa showed a positive trend both in terms of volume and export value. Meanwhile, the value of North Sumatra's rubber exports showed a constant trend (stagnant) indicating a positive trend. Palm oil, rubber, and cocoa produced by North Sumatra for export have strong competitiveness in the world market. This can be seen from the results of the calculation of the RCA value which is far above the value of one more than 0.